2019
DOI: 10.31219/osf.io/2m9h8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of public green space on acute psychophysiological stress response: a systematic review and meta-analysis of the experimental and quasi-experimental evidence

Abstract: Contact with nature is widely considered to ameliorate psychological stress, but the empirical support for a causal link is limited. We conducted a systematic review to synthesize and critically assess the evidence. Six electronic databases were searched. Twenty-six studies evaluated the difference between the effect of natural environments and that of a suitable control on the acute psychophysiological stress response. Eighteen studies were rated as being of moderate quality, 4 low quality, and 4 high quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Lastly, future research taking a strengths‐based approach by incorporating indices of natural environmental supports (e.g., green and blue spaces) and community resilience (e.g., neighborhood cohesiveness, women's health organizations, and family support networks) would appropriately balance the primarily risk‐focused line of inquiry we have discussed. Given past work showing the many physical and psychological health benefits associated with green/blue spaces (Crouse et al., 2018; Mygind et al., 2021; Thompson et al., 2012, 2014; Y. Zhang et al., 2020) and community social support (Anthony & O'Brien, 2002; Farrell et al., 2015; Wight et al., 2006), this is an important direction for future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Lastly, future research taking a strengths‐based approach by incorporating indices of natural environmental supports (e.g., green and blue spaces) and community resilience (e.g., neighborhood cohesiveness, women's health organizations, and family support networks) would appropriately balance the primarily risk‐focused line of inquiry we have discussed. Given past work showing the many physical and psychological health benefits associated with green/blue spaces (Crouse et al., 2018; Mygind et al., 2021; Thompson et al., 2012, 2014; Y. Zhang et al., 2020) and community social support (Anthony & O'Brien, 2002; Farrell et al., 2015; Wight et al., 2006), this is an important direction for future studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Here, I briefly review those health outcomes that may be related to facial appearance (see [3,6,[8][9][10][11][12] for further health states associated with RG).RG is negatively associated with oxidative stress markers [13,14], cardiovascular diseases [15,14,16], likelihood and severity of COVID-19 infections [17], and risk of inflammatory diseases [18]. Relatedly, stress, cortisol, and correlates are often lower in greener neighbourhoods ([19-21,3,22-24], but see also [6,25]). RG predicts mental health [26][27][28][29].…”
mentioning
confidence: 99%
“…Cardiovascular activity was used as a physiological measure of stress, following past research (Haluza et al, 2014;Mygind et al, 2019). The use of ECG measurements has been shown to be a valid reflection of participants' physiological states in virtual environments (Guger et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…It follows that natural environments rich in these resources elicit more positively toned affective states and reduce levels of physiological arousal, and can do so in a matter of minutes. The theory has been supported by a large body of research which shows that natural environments are associated with improved mood and reduced stress (for reviews, see Haluza et al, 2014;McMahan & Estes, 2015;Mygind et al, 2019). In one study, participants who walked in a nature reserve showed greater stress reduction, measured by blood pressure, and reported greater positive affect and lower anger compared to participants who walked in an office and retail urban setting .…”
Section: Stress Recovery Theorymentioning
confidence: 99%
See 1 more Smart Citation